An enabling environment for the national flour blending policy: A food systems analysis - Melesse, Mequanint B.; Tessema, Yohannis Mulu; Manyasa, Eric; Hall, Andrew (International Food Policy Research Institute, 2023)
A national flour blending policy is about to be implemented in Kenya. This requires maize flour (the country’s main staple) to be blended with at least 10 percent of either one or a composite of traditional crops, such as sorghum and millet.1 The blending ratio is expected to increase gradually, with the goal of ultimately reaching 30 percent. The policy envisages achieving several goals. The first is to improve the nutritional quality of maize flour: sorghum and millet (and other candidate blending crops) have micronutrient characteristics that are absent in maize. The second is to promote more climate-tolerant crops and technologies: sorghum and millet can be grown in less favorable arid and semiarid lands (ASALs), in the very conditions that many farmers face in Kenya. This is particularly important given that maize is more susceptible than other staple crops to climate change. The third is to reduce the country’s overreliance on imported maize and concerns about its food sovereignty.